Impact of the coronavirus infectious disease (COVID-19) pandemic on the provision of inflammatory bowel disease (IBD) antenatal care and outcomes of pregnancies in women with IBD. Issue 1 (22nd March 2021) - Selinger, Christian Philipp; Fraser, Aileen; Collins, Paul; Gunn, Melanie; Chew, Thean Soon; Kerry, Georgina; Patel, Kamal V; Roysam, Maya; Bel Kok, Klaartje; Bancil, Aaron; Hall, Veronica; Cooney, Rachel; et al.
Abstract : Background: The impact of COVID-19 on pregnant inflammatory bowel disease (IBD) patients is currently unknown. Reconfiguration of services during the pandemic may negatively affect medical and obstetric care. We aimed to examine the impacts on IBD antenatal care and pregnancy outcomes. Methods: Retrospective data were recorded in consecutive patients attending for IBD antenatal care including outpatient appointments, infusion unit visits and advice line encounters. Results: We included 244 pregnant women with IBD, of which 75 (30.7%) were on biologics in whom the treatment was stopped in 29.3% at a median 28 weeks gestation. In addition, 9% of patients were on corticosteroids and 21.5% continued on thiopurines. The care provided during 460 patient encounters was not affected by the pandemic in 94.1% but 68.2% were performed via telephone (compared with 3% prepandemic practice; p<0.0001). One-hundred-ten women delivered 111 alive babies (mean 38.2 weeks gestation, mean birth weight 3324 g) with 12 (11.0%) giving birth before week 37. Birth occurred by vaginal delivery in 72 (56.4%) and by caesarean section in 48 (43.6%) cases. Thirty-three were elective (12 for IBD indications) and 15 emergency caesarean sections. Breast feeding rates were low (38.6%). Among 244 pregnant women with IBD, 1 suspected COVID-19 infection was recorded. Conclusion: IBD antenatal care adjustments during the COVID-19 pandemic have not negatively affected patient care. Despite high levels of immunosuppression, only a single COVID-19 infection occurred. Adverse pregnancy outcomes were infrequent.